Nutritional Status of School Going Children in Relation to Their Dietary Intake at Mid-Morning - Akbar, Farah Naz; Lodhi, Asma; Mahmood, Shahid; Mueen-ud-Din, Ghulam; Murtaza, Mian Anjum (Pakistan Journal of Nutrition, 2015)
Present study was conducted to evaluate the quality of lunch box contents, BMI and eating behavior of school children. An informed consent was taken from parents after dissemination of study and then 150 students of both genders aged 6-11 years were randomly selected from a school, their height (m2) and weight (kg) was measured to calculate BMI (kg/m2). Lunch boxes were examined for their contents, 60 lunch boxes contained simple chips (SP), french fried chips (CF), packed chips (CP), chopri roti (R), allo wala paratha (PA), simple paratha (PS), boiled egg (EB), fry egg (EF) and omelet (EO) in common. Lunch boxes were analyzed for moisture, ash, crude protein, crude fiber, crude fat and nitrogen free extract (NFE). Result showed at the age of 11 years 33.3% children were overweight, 11.10% children were obese and only 44.40% normal weight. At the age of 10 years 3.7% children were overweight as well as obese and only 44.40% normal weight. At the age of 9 years 25% children were overweight and 54% children were normal weight. At the age of 8 years 4% children were overweight and 48% children were normal weight. While at the age of 6 years and 7 years no one child was overweight and nor was child obese. Dietary intake at mid-morning was also observed in which at the age of 11 years 78% children were using money for buying high fat lunch meal and 22% children took lunch box with them. At the age of 10, 9, 8, 7 and 6 years, respectively 50, 52, 18, 05 and 0% children were using money for buying high fat lunch meal and 27, 40, 70, 76 and 81% children took lunch boxes with them while 23, 8, 12, 19 and 19% children had no lunch as well money. Lunch boxes contents (%) contained moisture, ash, crude protein, crude fiber, crude fat and nitrogen free extract (NFE) 34.43±0.058, 0.631±0.020, 11.78±0.500, 0.34±0.10, 6.9±500 and 44.57±0.410, respectively. BMI of school going children were increased with age due to high consumption of fatty and vendor foods and lunch box avoiding behavior.